ANALISIS YURIDIS TERHADAP KONTEN PROMOSI LIVE SHOPPING TIKTOK PRODUK E-COMMERCE DALAM PERSPEKTIF HAK CIPTA - NIM. A1012201112, DIAN NORMALADEWI (Jurnal Fatwa Hukum, 2024)
Abstract  This research analyzes the juridical aspects of TikTok live shopping promotional content for e-commerce products from a copyright perspective. The main focus of the study is on the copyright protection mechanisms implemented by TikTok and the platform's actions in handling copyright infringement.                       The research methodology employed is normative juridical, encompassing analysis of laws and regulations, case studies, and review of TikTok policies.                       The research findings indicate that TikTok has implemented several copyright protection mechanisms. These mechanisms cover several interconnected key aspects to ensure copyright compliance. First, TikTok relies on advanced technologies such as automated content recognition systems and digital watermarking to detect and prevent unauthorized use of content. These systems can identify re-recorded content, even if modified, and can take immediate action such as restricting visibility or removing content. Second, the platform provides user-friendly reporting tools, including a one-click reporting system and a more detailed complaint form portal, allowing content owners to quickly report infringements. Third, TikTok has established a dedicated moderation team trained to handle copyright infringement cases, ensuring that each report is dealt with promptly and efficiently. Additionally, TikTok implements a proactive educational approach, providing guidance and information to creators and affiliators about the importance of respecting copyright. The platform also collaborates with industry and other platforms to share information and best practices in dealing with copyright infringement.The platform also provides a copyright infringement complaint system, although its effectiveness needs improvement. This study recommends refinements to TikTok's policies and increased user awareness about copyright in the context of e-commerce live shopping.Keywords: copyright, live shopping, TikTok, e-commerce, digital content     Abstrak                         Penelitian ini menganalisis aspek yuridis konten promosi live shopping TikTok untuk produk e-commerce dari perspektif hak cipta. Fokus utama penelitian adalah mekanisme perlindungan hak cipta yang diterapkan oleh TikTok dan tindakan platform dalam menangani pelanggaran hak cipta.                        Metodologi penelitian yang digunakan adalah yuridis normatif meliputi analisis peraturan perundang-undangan, studi kasus, dan tinjauan kebijakan TikTok.                        Hasil penelitian menunjukkan bahwa TikTok telah menerapkan beberapa mekanisme perlindungan hak cipta, Mekanisme ini mencakup beberapa aspek kunci yang saling terkait   untuk memastikan kepatuhan terhadap hak cipta. Pertama, TikTok mengandalkan teknologi canggih seperti sistem pengenalan konten otomatis dan watermarking digital untuk mendeteksi dan mencegah penggunaan konten tanpa izin. Sistem ini mampu mengidentifikasi konten yang direkam ulang, bahkan jika telah dimodifikasi, dan dapat mengambil tindakan segera seperti pembatasan visibilitas atau penghapusan konten. Kedua, platform ini menyediakan alat pelaporan yang mudah digunakan, termasuk sistem one-click reporting dan portal formulir pengaduan yang lebih detail, memungkinkan pemilik konten untuk dengan cepat melaporkan pelanggaran. Ketiga, TikTok telah membentuk tim moderasi khusus yang terlatih untuk menangani kasus-kasus pelanggaran hak cipta, memastikan bahwa setiap laporan ditangani dengan cepat dan efisien. Selain itu, TikTok juga menerapkan pendekatan edukasi proaktif, memberikan panduan dan informasi kepada kreator dan affiliator tentang pentingnya menghormati hak cipta. Platform ini juga bekerja sama dengan industri dan platform lain untuk berbagi informasi dan praktik terbaik dalam menangani pelanggaran hak cipta.. Platform ini juga menyediakan sistem pengaduan pelanggaran hak cipta, meski efektivitasnya perlu ditingkatkan. Studi ini merekomendasikan penyempurnaan kebijakan TikTok dan peningkatan kesadaran pengguna tentang hak cipta dalam konteks live shopping e-commerce.    Kata kunci: hak cipta, live shopping, TikTok, e-commerce, konten digital